2021
DOI: 10.3390/antibiotics10080988
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-Associated Pneumonia in COVID-19 Patients: A Retrospective Cohort Study

Abstract: Introduction: Aim of this study is to analyse the characteristics of ventilator-associated pneumonia (VAP) inpatients infected by severe acute respiratory syndrome-coronavirus 2 (SARS-Cov2). Materials and Methods: A retrospective study was conducted, including coronavirus infectious disease 2019 (COVID-19) patients who developed VAP from March to May 2020 (VAP COVID-19). They were compared to non-COVID-19 patients who developed VAP from January 2011 to December 2019 (VAP NO COVID-19) and COVID-19 patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
3
20
1
Order By: Relevance
“…However, the evidence from this trial, although not adequately powered, suggests potential beneficial effects of inhalation therapy on the incidence of Gram-positive bacterial VAP, a finding which should be confirmed in further studies. Although the most common causes of VAP are Gram-negative bacteria, MRSA causes approximately 7% of VAP [42][43][44]. The present study found even higher incidence of MRSA VAP in the control group (up to 35%), highlighting the importance of this pathogen in critically ill COVID-19 patients.…”
Section: Discussionsupporting
confidence: 46%
“…However, the evidence from this trial, although not adequately powered, suggests potential beneficial effects of inhalation therapy on the incidence of Gram-positive bacterial VAP, a finding which should be confirmed in further studies. Although the most common causes of VAP are Gram-negative bacteria, MRSA causes approximately 7% of VAP [42][43][44]. The present study found even higher incidence of MRSA VAP in the control group (up to 35%), highlighting the importance of this pathogen in critically ill COVID-19 patients.…”
Section: Discussionsupporting
confidence: 46%
“…How do we reconcile the various previous studies that have reported a significant increase in VAP rates in patients with COVID-19 (2)(3)(4)(5)(6)(7)(8)(10)(11)(12)(13)(14) with this finding of no increase from Hedberg et al (9)? The first explanation may be related to the very high rate of VA-LRTI in the control arm of Hedberg et al (9) study: 34 per 1,000 ventilation-days, compared with lower control arm rates from previous studies: 13 per 1,000 ventilation-days (3) and 15 per 1,000 ventilation-days (2), which indicates that Hedberg et al (9) reported more than double the control baseline rate of other studies; thus, if patients without COVID-19 were already at such a high risk for VAP (9), it might have become not feasible to detect any VAP rate difference compared with patients with COVID-19.…”
mentioning
confidence: 49%
“…After excluding 632 due to duplication or because they did not meet the inclusion criteria based on the title and abstract, we found 60 relevant articles that were considered for full-text review and eligibility. Finally, 25 articles that met the criteria were included in this systematic review [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The flow chart of the systematic literature search according to PRISMA guidelines is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%